Reconciling the value of the elevator round trip time between calculation and simulation. (August 2017) - Al Sukkar, Ghazi; Al-Sharif, Lutfi; Mansour, Mahmoud; Gharbieh, Mohammad; Farraj, Esraa; Jarrah, Rawan; Milekh, Rasha; Zaben, Noor
This paper attempts to understand the reasons for the difference in the value of the round trip time between calculation and simulation. It is posited the main reason for the difference is the combination of two factors: the restricted car capacity and the randomness in the behavior of the elevator traffic system, thus leading to a reduced effective car loading (effectively based on a smaller number of passengers in the car). There are three sources of randomness in the behavior of the system: the randomness of the passenger destinations (thus making the value of the round trip time a random variable), the randomness of the passenger arrival (driven by a Poisson passenger arrival model), and the effect of elevator bunching (thus making the value of the interval a random variable). Using a MATLAB-based simulator, the value of the round trip time is plotted against the system loading level for the case of a single entrance and incoming traffic only. Different conditions are simulated, including constant and random passenger arrivals, as well as queues-allowed and queues-not-allowed conditions. Varying these conditions provides an essential insight into the variation of the round trip time and the reasons for it. The effect of the number of passengers boarding the elevator on the value of the round trip time (and thus on the value of the system handling capacity) is investigated in more detail.